2009
DOI: 10.1017/s1751731109004455
|View full text |Cite
|
Sign up to set email alerts
|

Effect of supplementation of the maternal diet with fish oil or linseed oil on fatty-acid composition and expression of Δ5- and Δ6-desaturase in tissues of female piglets

Abstract: The present study investigated whether enrichment of the pig maternal diet with n-3 polyunsaturated fatty acids (PUFA) affects the fatty-acid composition of female piglets via enhancing of expression of the lipogenic enzymes D5-desaturase (D5d) and D6-desaturase (D6d). The sows (50% Landrace 3 50% Large White) were fed a control diet or one of the experimental diets starting at day 45 in gestation. The experimental diets were supplemented either with linseed oil or fish oil, whereas the control diet contained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
26
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 44 publications
9
26
0
Order By: Relevance
“…Higher DHA levels in the brain could lead to increased postnatal growth rates due to a change in behavior. DHA concentration was also increased in liver and Semitendinosus muscle tissues of pigs from treated sows, which is again in agreement with other reported findings (Rooke et al, 2000 and2001a;Missotten et al, 2009) and confirms that DHA must have been available to the fetus during gestation. This is in agreement with our previous findings that EPA and DHA were higher in serum during gestation in gilts fed mLCPUFA, and that DHA concentration was increased in embryos at day 30 of gestation (Smit et al, 2013a).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Higher DHA levels in the brain could lead to increased postnatal growth rates due to a change in behavior. DHA concentration was also increased in liver and Semitendinosus muscle tissues of pigs from treated sows, which is again in agreement with other reported findings (Rooke et al, 2000 and2001a;Missotten et al, 2009) and confirms that DHA must have been available to the fetus during gestation. This is in agreement with our previous findings that EPA and DHA were higher in serum during gestation in gilts fed mLCPUFA, and that DHA concentration was increased in embryos at day 30 of gestation (Smit et al, 2013a).…”
Section: Discussionsupporting
confidence: 92%
“…This suggests preferential uptake of DHA over EPA by the brain. EPA was increased in liver, which is in agreement with Rooke et al (2000 and2001a) and Missotten et al (2009). EPA was only increased in the Semitendinosus muscle when expressed as percent of total fatty acids, while Missotten et al (2009) found increased EPA when expressed as mg/100 g tissue.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our earlier study on pigs demonstrated that diets, including PUFA-supplemented diets, can trigger changes in the expression of lipogenic enzymes, and these changes are related to variations in fatty acid profiles (Doran et al, 2006;Missotten et al, 2009). Regulatory effects of the dietary fatty acids on enzyme expression have also been demonstrated in experiments on laboratory animals and on human (Jump and Clarke, 1999;Ntambi, 1999).…”
Section: Discussionmentioning
confidence: 94%
“…Indeed, Missotten et al (2009) showed that expression of D5-and D6-desaturase was tissue-specific, which the authors suggested was, at least partially, the reason for differences seen in n-3 LCPUFA levels between tissues.…”
Section: Discussionmentioning
confidence: 99%